Gender and Technological Failures in Glitch Music. Issue 1 (2nd January 2016) - Bosma, Hannah
Abstract : Currently, there is a (re-)emergence of theoretical work on glitch in art and culture. With its 'aesthetics of failure' and Deleuzian theoretical orientation, glitch music seems to stand for an alternative approach to sound technology and music that does not conform to hegemonic masculinity. However, closer inspection reveals that many aspects of glitch are conventionally gendered as masculine: mostly male protagonists; a narrow focus on technology, tools and innovation; a tendency towards abstraction and minimalist (quasi-)modernist aesthetics. 'Failure' features in glitch music as a heuristic device and serves as the basis for the development of a new style or movement, new 'territories', new techniques, new software tools and new sound material. Through recording, processing, editing and sequencing, the glitches are domesticated. The masculinity of glitch music is one of men creating new practices and opportunities in a male environment. While the alternative conception of sound technology displayed by the work of female artists such as Huba de Graaff and Cathy van Eck is broad and hybrid and takes the situatedness of its practices into account, glitch music displays a narrow notion of both technology and music.